2016
DOI: 10.1111/aec.12349
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between fire and introduced deer herbivory on coastal heath vegetation

Abstract: The coastal heathlands of the Royal National Park are impacted by both fire and herbivory by introduced deer, and to date these two factors have been dealt with independently in the management of natural areas. In recent years, there has been increasing recognition for a more integrated approach to manage these two disturbance agents. Fire and its role in Australian heathlands are well known, while impacts from introduced deer and the combined effects of fire and introduced deer are still poorly understood. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Knowledge of modifications to vegetation communities by large herbivores within fire‐prone ecosystems is increasing (Crowther et al, 2016 ; Tuft et al, 2012 ). We found that post‐fire herbivory reduced plant species richness, diversity, and evenness and increased plant dominance measures.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of modifications to vegetation communities by large herbivores within fire‐prone ecosystems is increasing (Crowther et al, 2016 ; Tuft et al, 2012 ). We found that post‐fire herbivory reduced plant species richness, diversity, and evenness and increased plant dominance measures.…”
Section: Discussionmentioning
confidence: 99%
“…Crowther et al . (2016) also observed that the coverage of sedges and grasses was lower at sites where deer were present, compared to sites where deer were absent. Cycads have not been frequently recorded as components of either deer or macropod diets, making it unclear which group is responsible for the recorded grazing pressure.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, rusa deer in Royal National Park affected the structure and composition of heathlands, and reduced coverage of grasses, sedges and low vegetation (Crowther et al . 2016). Coverage of medium and tall shrubs also varied with fire history and the presence of rusa deer (Crowther et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation